Navigating involvement spaces: The impact of campus environment on multiracial identity development. Issue 174 (5th November 2021) - Stites, Alicia K.; Khan, Mohammad‐Mehdi A.; Dean‐Scott, Shannon R.
Abstract: This article presents the experiences of Multiracial students at a Hispanic Serving Institution (HSI) and the unique challenges they face in exploring their racial identities and finding belonging.